2013
DOI: 10.1186/2193-1801-2-528
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of an abbreviated training program for health workers in breast cancer awareness: innovative strategies for resource constrained environments

Abstract: BackgroundBreast cancer is characterized by late presentation and significant morbidity and mortality in developing countries. Breast screening aids in early detection of breast cancer. Nurses are uniquely placed to provide advocacy and screening in a resource limited environment.ObjectivesTo assess the effectiveness of an abbreviated training program in breast cancer awareness on nurses at a tertiary hospital, in a resource constrained environment.MethodsUsing a statistical tool, the Solomon Model, 79 nurses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…In lower- and middle-income countries (LMICs), a patient’s first encounter with the health system often is with a community health worker (CHW) at the dispensary (community) level; however, CHW and nurses’ knowledge of cancer and cancer risk factors, signs, and symptoms in many LMICs is low. [ 8 9 10 11 ] Oncology nurses placed throughout the country could dramatically increase the number of cases diagnosed in early stages. In addition, oncology nurses can educate CHWs about cancer to raise awareness and appropriately refer a patient for further evaluation.…”
Section: The Role Of the Nurse In Cancer Carementioning
confidence: 99%
See 1 more Smart Citation
“…In lower- and middle-income countries (LMICs), a patient’s first encounter with the health system often is with a community health worker (CHW) at the dispensary (community) level; however, CHW and nurses’ knowledge of cancer and cancer risk factors, signs, and symptoms in many LMICs is low. [ 8 9 10 11 ] Oncology nurses placed throughout the country could dramatically increase the number of cases diagnosed in early stages. In addition, oncology nurses can educate CHWs about cancer to raise awareness and appropriately refer a patient for further evaluation.…”
Section: The Role Of the Nurse In Cancer Carementioning
confidence: 99%
“…In addition, oncology nurses can educate CHWs about cancer to raise awareness and appropriately refer a patient for further evaluation. [ 8 12 ] Thus, nurses can act more efficiently as patient navigators through the continuum of care to link the patient to local health systems and decrease delay in care. [ 13 14 ]…”
Section: The Role Of the Nurse In Cancer Carementioning
confidence: 99%
“…[13][14][15][16][17][18][19] Healthcare professionals are essential contributors in promoting breast cancer awareness among their communities. [20][21][22][23] In addition to their educational roles, health workers could encourage and guide women through appropriate screening tools and their availability. Pharmacists represent a major sector of healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…35 Other studies have also demonstrated the efficacy of training community health workers in the early detection and referral of breast and cervical cancer. [35][36][37][38][39][40][41] Whether such interventions in the adult cancer space can translate effectively to improvments in the early detection of childhood cancers in LMICs is a subject for future research. is thus dependent on cancer type and jurisdiction.…”
Section: Discussionmentioning
confidence: 99%